Pengaruh Retribusi Izin Mendirikan Bangunan (IMB) Terhadap Pendapatan Asli Daerah (PAD) Kabupaten Rejang Lebong - Gustini Gustini; Azuwandri Azuwandri; Salehan Salehan; M Bima Eka Putra (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2023)
Regional Own Revenue is part of regional revenue sources which can be freely used by each region to organize regional government and development. Regional levies are local revenues from payments for services or the granting of certain special permits granted by the local government. Therefore, the purpose of this study was to determine the effect of building permit fees (IMB) on local revenue (PAD) in Rejang Lebong Regency. In this writing, the type of research used is descriptive research and the data collection method used is documentation. The analytical method used is simple linear regression, simple correlation, and termination. The results of this study are that the effect of building permit fees (IMB) on local revenue (PAD) in Rejang Lebong Regency is quite good. With the tendency of revenue realization to increase every year, with an average rate of 1.16%. The regression results show that the effect of IMB levies on achieving the PAD target is positive. The correlation value indicates the close relationship between the IMB levy and the achievement of the PAD target is moderate. The result of the termination test is that the IMB levy affects the achievement of the PAD target of 35%. The results of the hypothesis test show that the IMB levy does not significantly affect the achievement of the PAD target, this is because the target and realization of the IMB levy are still small and statistically have not shown a clear influence